KARAKTERISTIK TEH INSTAN BUNGA KAMBOJA SUDAMALA (Plumeria rubra) YANG DIPRODUKSI DENGAN TEKNIK KOKRISTALISASI - Sholeha, Lianatus; Wrasiati, Ni Luh Putu; Ganda Putra, G.P (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2014)
The aims of this study were to (1) determine the effect of saturated sugar and comparison with saturated sugar solution and the “Sudamala” frangipani extract on solution on the characteristics of instant tea “Sudamala” frangipani flower, and (2) to obtain additional saturated sugar and comparison of “Sudamala” frangipani flower extract with saturated sugar solution that have the best characteristics of instant tea “Sudamala” frangipani flower. This study used factorial completely randomized design. The first factor consists of the addition of saturated sugar: (cane sugar and palm sugar), the second factors were“Sudamala” frangipani extract comparison with saturated sugar solution consists of (3:10, 4:10, 5:10, and 6:10). The experiment was repeated 2 times. The extraction process is done by maceration method using a manufacturing process while cocristalisasi techniques. The observed variables are moisture content, ash content, total sugar, rehydration time, insoluble solids and organoleptic tests. Addition of saturated sugar affect the moisture content, ash content, total sugars, insoluble solids and rehydration time. The addition of “Sudamala” frangipani flower extract effect on moisture content and ash content , has no effect on total sugars, insoluble solids and rehydration time. The interaction between the treatment effect on water content, testing aroma, color, and overall acceptance has no effect on the moisture content, ash content, total sugars, insoluble solids, rehydration time and taste test. Addition of brown sugar and comparison “Sudamala” frangipani flower extract 3:10 with sugar solution that has the best characteristics of instant tea
Keywords: 17